2019
DOI: 10.1542/peds.2018-2242
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Trajectories of Cardiovascular Health Indicators During Early Childhood

Abstract: OBJECTIVES: Cardiovascular disease prevention should begin in childhood. However, the influence of physical activity on cardiovascular health in early childhood is unknown. Our purpose in this study was to determine the effect of physical activity on trajectories of cardiovascular health indicators during early childhood. METHODS: This prospective, observational cohort study (Health Outcomes and Physical Activity in Preschool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 51 publications
4
33
2
Order By: Relevance
“…The main instruments used were questionnaires and accelerometers. 44,45 In our results, the majority of studies report insufficient levels of MVPA 17,37,39,41-43 ; however, this insufficiency is concordant with the general population.…”
Section: Discussionsupporting
confidence: 74%
“…The main instruments used were questionnaires and accelerometers. 44,45 In our results, the majority of studies report insufficient levels of MVPA 17,37,39,41-43 ; however, this insufficiency is concordant with the general population.…”
Section: Discussionsupporting
confidence: 74%
“…Nine out of 39 studies were rated as high methodological quality [ 18 , 20 , 21 , 23 , 27 , 28 , 31 33 ], eight studies were rated as moderate quality [ 16 , 17 , 19 , 22 , 24 26 , 29 ] and 22 studies were rated as weak methodological quality [ 30 , 34 54 ]. Figure 2 displays a summary of the methodological quality across included studies per outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies examined the association between physical activity and cardiometabolic health indicators such as blood pressure [ 27 , 33 , 36 , 42 ], biomarkers [ 30 , 32 , 33 ] and physical fitness [ 16 , 27 ], of which two studies were intervention studies [ 36 , 42 ] (See Table 1 and Table S 4 ). Physical activity was measured objectively in four studies [ 16 , 27 , 32 , 33 ] and subjectively in three studies [ 30 , 36 , 42 ]. Three studies were rated as high methodological quality [ 27 , 32 , 33 ], one study was rated as moderate methodological quality [ 16 ] and three studies were rated as weak methodological quality [ 30 , 36 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the population was sampled to be representative of the US. Most recently, Proudfoot et al 43 measured physical activity and fitness in a very young cohort (3‐5 years old) and found that higher levels of fitness, even in young children, were associated with better cardiovascular health indicators including decreased arterial stiffness. One limitation of this study is the cross‐sectional design, and, thus, we are unable to establish temporal relationships between aerobic fitness, sedentary time, and asthma outcomes.…”
Section: Discussionmentioning
confidence: 99%